Studies on Chemical Characterization of Ginkgo Amillaria Oral Solution and Its Drug–Drug Interaction With Piceatannol 3′-O-β-D-Glucopyranoside for Injection - Yu, Zhenyan; Hu, Xiaohan; Zhou, Lin; Chen, Huliang; Xing, Yanchao; Han, Chunyue; Ding, Hui; Han, Lifeng; Pan, Guixiang; Fu, Zhifei (Frontiers in Pharmacology, 2022)
Ginkgo Amillaria oral solution (GAO) is commonly used for the treatment of cardiovascular and cerebrovascular diseases in China. Piceatannol-3'-O-β-D-glucopyranoside for injection (PGI) is mainly used for the prevention and treatment of ischemic cerebrovascular diseases. With the spread of cerebrovascular disease, the possibility of combining the two drugs has increased, however, there is no research on the drug-drug interaction (DDI) between these two medicines. In this paper, an ultra-high performance liquid chromatography/quadrupole-orbitrap mass spectrometry (UHPLC/Q-Orbitrap MS) method was established to characterize the chemical constituents of GAO firstly, 62 compounds were identified or tentatively identified based on their retention time (RT), MS and MS/MS data. Nine main compounds were determined by ultra-high performance liquid chromatography/triple quadrupole mass spectrometry (UPLC-QQQ-MS). Furthermore, the incubation with liver microsomes in vitro were fulfilled, the results showed that GAO had significant inhibitory effect on UGT1A9 and UGT2B7 (p ＜ 0.05), and PGI was mainly metabolized by UGT1A9. The identification results of in vivo metabolites of PGI showed that PGI mainly undergoes a phase II binding reaction mediated by UDP-glucuronosyltransferase (UGT) and Sulfotransferase (SULT) in vivo. Therefore, pharmacokinetics studies were fulfilled to investigate the DDI between GAO and PGI. The results showed that the AUC (p ＜ 0.05) and T1/2 (p ＜ 0.05) of PGI in vivo were significantly increased when administrated together with GAO, while the CL was significantly decreased (p ＜ 0.05). The exploration of in vitro and in vivo experiments showed that there was the DDI between GAO and PGI.